Meretas Pola Menunda: Tinjauan Strategi Intervensi Prokrastinasi dalam Pembelajaran - Yudith Wina Herlita Susanto; Careen Ayudiah Kusuma; Fathin Fathia Kamila Qotrunad; Muhammad Arkan Faizal; Najwa Razita Denaputri (Journal of Gender Equality and Social Inclusion (gesi), 2025)
Academic procrastination is a behavior of delaying completing academic obligations that can have a negative impact on an individual's achievement and mental health. This study aims to examine the factors that cause academic procrastination and effective intervention strategies in the context of education. Through a systematic literature review, it was found that poor time management, low learning motivation, and other psychological factors contribute significantly to procrastination behavior. Various intervention approaches, such as self-management based on Cognitive Behavior Therapy (CBT), client-centered counseling, and Solution Focus Brief Counseling (SFBT), have been shown to be effective in reducing the level of procrastination. However, the application of these interventions in educational settings is still limited. This study recommends the development of more systematic and applicable intervention programs, as well as the active role of teachers and counselors in supporting students to overcome procrastination. Thus, it is hoped that a more conducive learning environment can be created that supports students' time management and adaptive behavior.